Pengaruh Overclaim Dan Persepsi Merek Terhadap Loyalitas Konsumen Gen Z Pada Iklan Skincare Di Shopee Dengan Kepuasan Konsumen Sebagai Variabel Intervening - Victoria .; Emil Salim; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of overclaim and brand perception on Generation Z consumer loyalty toward skincare advertisements on Shopee, with customer satisfaction as an intervening variable. This research employed a quantitative approach using a survey method involving 100 Generation Z respondents who had viewed skincare advertisements on Shopee and purchased skincare products through the platform. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that overclaim does not have a significant direct effect on consumer loyalty, whereas brand perception has a positive and significant effect on consumer loyalty. In addition, overclaim has a negative and significant effect on customer satisfaction, while brand perception has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on consumer loyalty and is able to mediate the influence of overclaim and brand perception on consumer loyalty. These findings indicate that customer satisfaction plays an important role in building Generation Z consumer loyalty toward skincare products advertised on Shopee. This study is expected to provide theoretical contributions to consumer behavior research and practical implications for business practitioners in designing more effective advertising and brand management strategies on the Shopee platform.